ANALISIS POTENSI SEKTOR BASIS DAN NON BASIS KABUPATEN PAYAKUMBUH TAHUN 2018-2021 - Agus Supriadi; Muhadan Nurvianto; Ahmad Syukron Prasaja (Al-Ijtima`i: International Journal of Government and Social Science, 2022)
To improve the economic performance of a country, the growth of Produk Domestik Regional Bruto (PDRB)from various industries can be used. This Produk Domestik Regional Bruto (PDRB)growth occurs if the area has a leading sector or basic sector with a relatively fast growth rate and has strong competitiveness and non-base sectors are encouraged to become the basic sector if this study uses time series data from the BadanPusatStatistik (BPS) ProvinceSumatra, Indonesia, the period of four years 2018 to 2021. The purpose of this study is to identify the fundamental and non-fundamental sectors of the economic structure of the Payakumbuh region between 2018 and 2021. This is done using the location quotient analysis method and the dynamic location quotient method ( DLQ).